Crafting Jobs on Job Satisfaction to Encourage Employee Development of IAIN Palopo - Kaimuddin Kaimuddin (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The results of the audit of the Inspectorate General of the Ministry of Religion in 2020 showed the performance achievement of IAIN Palopo was only 76.14%, and several sources stated that the performance of higher education was strongly motivated by job satisfaction which was influenced by the ability of its employees to innovate in their work. Therefore, this study will analyze job satisfaction and work innovation (job crafting), which will be a reference to improving IAIN Palopo. This study uses quantitative methods with a sample of 135 employees of IAIN Palopo. The results showed that job crafting affected the job satisfaction of IAIN Palopo employees.